Cohesion policy and the principle of subsidiarity: A legal analysis - Päivi Leino-Sandberg (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This report addresses the legal aspects of how the EU's Cohesion Policy has changed over the past decade, exploring the legal argumentation behind its transformation. Cohesion Policy used to be understood as a policy with distinct features and clear limits, characterised by its focus on reducing disparities between the levels of development of the various regions and the backwardness of the least favoured regions (ar>cle 174 TFEU), but with Treaty-based linkages to environmental aims and trans-European networks. Cohesion Policy has relied on national co-funding and engaging local and regional actors. The 2021-2027 MFF, and in particular the NGEU, took Cohesion Policy in a completely different direction. The first sec>on of the Report demonstrates how this change has (in practical terms, without a formal Treaty amendment) affected the division of competence between the EU and its Member States and the application of the principle of subsidiarity. Cohesion Policy now stretches to nearly anything that the EU funds, irrespective of any pre-existing competence limitations. The Report explains in detail how the interpretation of the EU's competence in Cohesion Policy was gradually broadened in the instiutions without public debate. This examinaton is based on previously undisclosed internal legal advice and Court pleadings used by the Commission and Council, to which the institutions have granted public access for the purposes of this Report. The Report then analyses the scope and uses of RRF funding, its design as 'money for reforms' the effect of this funding on subsidiarity and finally questions whether any legal constraints remain or are relevant aUer the transformation of Cohesion Policy through the NGEU. In the ongoing mid-term review of the MFF the Commission draws attention on to numerous pressing funding needs of a European dimension. At the same time, the largest EU funding vehicle to a large extent ignores these broader European priori>es, both in law and in practice. Finally, the Report looks at the future of EU funding and argues for the introduction of new delimiting principle for how EU funding should be used in the future, involving in particular a more fundamental consideration of the European added value of measures to be funded.
Keywords: 330; EU Treaties; Cohesion policy; NextGenerationEU; Recovery and Resilience Facility; European Commission; EU budget; subsidiarity